Tortilla Flat Still - MGM:::Creator::::::::::::
From left to right: Tito Ralph (Sheldon Leonard), Pablo (Akim Tamiroff), Pilon (Spencer Tracy), and Danny Alvarez (John Garfield) stand, discussing a vase. RESTRICTED USE Digital copy only. No hard copy.